Adrenal gland‐released vasostatin‐I is a myocardial depressant factor. Issue 4 (3rd February 2020) - Schneider, Francis; Castelain, Vincent; Herbrecht, Jean‐Etienne; Hellé, Sophie; Metz‐Boutigue, Marie‐Hélène
Abstract : Pheochromocytoma crisis is an exceptional consequence of the release of storage vesicles of the adrenal medulla. It is complicated by fulminant adrenergic myocarditis. It offers a unique opportunity to detect inotropic negative factors from neuroendocrine origin. Our objectives were (a) to describe a pheochromocytoma crisis, (b) to investigate in vivo myocardial depressant activities for the N‐terminal 1‐76 Chromogranin A‐derived peptide, vasostatin‐I (VS‐I). A patient with a pheochromocytoma crisis was treated, including extracorporeal membrane oxygenation, until mass resection. Plasma concentrations of VS‐I were time‐dependently assessed with a specific immunoassay; correlations with invasive cardiovascular parameters were investigated. Increased VS‐I concentrations were observed over 7 days until tumour resection. VS‐I concentrations correlated positively with Chromogranin A levels, negatively with cardiac output and left ventricular stroke work index, but not with heart rate. This case illustrates the pharmacokinetics of VS‐I in a pheochromocytoma crisis. It highlights myocardial depressant activity for this peptide at high concentrations.